Iatrogenic Small Bowel Hemorrhage Treated With Transcatheter Arterial Embolization - Nguyen Vu Dang; Si, Bui Tien (Journal Of Cardiovascular, Neurovascular & Stroke, 2024)
Case presentation: A 74 years-old male patient had abdominal pain. He was diagnosed with cholangitis and biliary obstruction due to pacreatic head tumor. He then experienced a Whipple surgery for the pacreatic head and D2 duodenal removal, choledochojujenal anastomosis. Elevent days after the surgery, he had a hypovolemic shock with a hemoperitoneum. There was a suspicious bleeding from the resected arteries at the sutured sites. An abdominal computed tomography angiography (CTA) was performed and the hemorrhagic pseudoaneurysmal artery was identified. He was immediately sent to the angio-suite for the embolization. The bleeding branch of the right gastric artery carrying a pseudoaneurysm was embolized with 2 coils. Check angiogram show complete oclusion of the pseudoaneurysm without any complications. He was doing well after the procedure and was discharged uneventfully after several days. Conclusion: Transcatheter aterial embolization had shown its effectiveness in the treatment of the postoperative iatrogenic gastrointestinal bleeding. Its technical simplicity makes it more advantageous outweighting a repeat of a surgery especially in the high-risk patients with multiple comorbidities. The development of interventional devices and technology are able to facilitate the procedure, reducing procedure time and could make it be the first-line treatment for the dilematic cases.